2020
DOI: 10.3389/fmed.2020.00319
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ultrasonography Compared to Conventional Radiography for the Diagnosis of Osteoarthritis in Patients With Knee Pain

Abstract: To investigate the performance of ultrasonography (US) for the detection of knee osteoarthritis (OA) in patients suffering from knee pain, compared to conventional radiographs. Methods: Cross-sectional study performed at a university teaching hospital. Consecutive patients complaining of unilateral or bilateral mechanical knee pain who signed an informed consent were included. All patients underwent simultaneously an ultrasonographic and a radiographic evaluation of the knee. Exclusion criteria were age under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Interestingly, Malas et al in 2014 [33] reported that a positive correlation was discovered between US meniscal extrusion measurements and radiological KL grade. This was also reported by Brom et al [34] concluding that US is a valid method with high sensitivity and specificity for detecting radiographic KOA.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, Malas et al in 2014 [33] reported that a positive correlation was discovered between US meniscal extrusion measurements and radiological KL grade. This was also reported by Brom et al [34] concluding that US is a valid method with high sensitivity and specificity for detecting radiographic KOA.…”
Section: Discussionsupporting
confidence: 79%
“…Joint cavity injection therapy is widely used, but the clinical efficacy is still controversial; excessive use of hormones may also lead to the risk of steroid arthropathy (7). Improving symptoms with prevention programmers is key to minimizing the social burden of KOA (8,9). Exercise therapy, as an active treatment recommended by the American Rheumatology Guidelines with strong evidence (10), is increasingly used by clinical staff for the prevention and treatment of KOA.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, we must improve imaging interventions based on, for example, clinical biomarkers, such as synovial hypertrophy, joint effusion, and involvement of tendons and ligaments. 78 Finally, to capture relevant changes, early or intermediate outcome measurements should be tailored to the clinical phenotypes of OA. 79…”
Section: Discussionmentioning
confidence: 99%